Managing Discretionary Accruals and Book‐Tax Differences in Anticipation of Tax Rate Increases: Evidence from China. (June 2015) - Wong, Raymond M. K.; Lo, Agnes W. Y.; Firth, Michael
Abstract This paper investigates how firms manage their earnings to trade off various incentives when tax rates increase. We hypothesize and find that firms generally choose to manage their taxable income upward in a book‐tax non‐conforming manner rather than in a book‐tax conforming manner before a tax rate increment, which in turn reduces the detection risk of aggressive financial reporting. These results suggest that firms give more weight to tax incentives and tax audit or regulatory inspection risks than to boosting financial reporting income in tax management. However, when firms have higher book management incentives or lower tunneling incentives (i.e., non‐state‐owned enterprises), we find that they manage their taxable income and book income upward together (i.e., in a book‐tax conforming manner), whereas their counterparts (i.e., state‐owned enterprises) do not. Overall, our paper contributes to the literature by demonstrating the interplay of tax, tunneling and financial reporting incentives in influencing tax management strategies. The findings from our paper should also help government and regulators understand more about firms' reactions to tax rate increases.